2019
DOI: 10.1002/ajmg.a.61065
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the functions of novel mutations in RAB3GAP1 in Martsolf and Warburg micro syndromes

Abstract: Purpose: Martsolf (MS) and Warburg micro syndromes (WARBM) are rare autosomal recessive inherited allelic disorders, which share similar clinical features including microcephaly, intellectual disability, brain malformations, ocular abnormalities, and spasticity. Here, we revealed the functions of novel mutations in RAB3GAP1 in a Turkish female patient with MS and two siblings with WARBM. We also present a review of MS patients as well as all reported RAB3GAP1 pathogenic mutations in the literature. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…However, low birth weight is not a sine qua nonfinding in the other reported cases. The c.2187_2188delinsCT variation, which was previously reported in two patients by Koparir et al, was also identified in P3, P4, and P5 (Koparir et al, 2019). Those 9-and 12-year-old patients had postnatal onset growth retardation including the height was below À3 SD, weight below À2.5 SD, and OFC below À5 SD, subsequent to normal birth measurements.…”
Section: Discussionsupporting
confidence: 65%
“…However, low birth weight is not a sine qua nonfinding in the other reported cases. The c.2187_2188delinsCT variation, which was previously reported in two patients by Koparir et al, was also identified in P3, P4, and P5 (Koparir et al, 2019). Those 9-and 12-year-old patients had postnatal onset growth retardation including the height was below À3 SD, weight below À2.5 SD, and OFC below À5 SD, subsequent to normal birth measurements.…”
Section: Discussionsupporting
confidence: 65%
“…Spastic quadriplegia has been reported in WARBM, whereas in Martsolf syndrome, spasticity is limited to lower limbs [56]. Molecularly, mutations reported in association with WARBM are mostly predicted to result in NMD and/or loss-of-protein-function [57]. On top of that, we also found that some clinical features, e.g.…”
Section: Discussionsupporting
confidence: 52%
“…However, the involvement of epigenetic or environmental factors cannot be ruled out. In view of all molecularly defined families with Martsolf, four had mutations in RAB3GAP2 , 3,6,12 two had mutations in RAB3GAP1 , 3,13 and one family had a mutation in TBC1D20 14 . In addition, Gumus reported a family with overlapping features of the two syndromes due to a splice site mutation in RAB3GAP2 gene 11 …”
Section: Discussionmentioning
confidence: 99%
“…Till now, around 100 families from diverse ethnic groups were molecularly confirmed as Micro syndrome where mutations in RAB3GAP1 were the most common cause (frequency 75%) 3,9,10 . As for Martsolf syndrome, RAB3GAP2 mutations have been described in five families, 3,6,11,12 while RAB3GAP1 and TBC1D20 mutations were found in two and one families, respectively 3,13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation